Probing the Electrochemical Properties of Graphene Nanosheets for Biosensing Applications - Alwarappan, Subbiah; Erdem, Arzum; Liu, Chang; Li, Chen-Zhong (Journal of physical chemistry. C, 2009)
In the present work, chemically synthesized graphene nanosheets were used as electrode materials and their electrochemical properties were systematically characterized. The surface morphologies of graphene nanosheets were evaluated using Raman spectroscopy and transmission electron microscopy. The results obtained were compared with that of single-walled carbon nanotubes (SWCNTs). Results indicated that the surface of graphene possesses greater sp2 character than the SWCNTs. Using a four-point probe technique, we found the conductivity of graphene particles to be 64 mS cm−1, which is approximately 60 times better than that of SWCNTs. Following this, different charged redox species were employed for the characterization of redox properties of the graphene thin film. Results indicated that the density of surface negative charge present on graphene surface is more than that found in SWCNTs. Furthermore, the possibility of employing graphene for the electrochemical detection of important neurotransmitters such as dopamine and serotonin was evaluated and compared with SWCNTs. In all these experiments, graphene exhibited a better sensitivity, signal-to-noise ratio, and stability than SWCNTs. In addition, graphene electrodes exhibited a superior biosensing performance than SWCNTs toward dopamine detection in the presence of common interfering agents such as ascorbic acid and serotonin. Our results demonstrate the potential of using graphene nanosheets as a new generation of biosensing materials.